2009
DOI: 10.1016/j.jcmg.2008.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging for Efficacy of Pharmacologic Intervention in Myocardial Remodeling

Abstract: Radiolabeled CRIP allows for the evaluation of the efficacy of neurohumoral antagonists after MI and reconfirms superiority of combination therapy. If proven clinically, molecular imaging of the myocardial healing process may help plan an optimal treatment for patients susceptible to heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 33 publications
1
45
0
2
Order By: Relevance
“…In the subsequent study, 99m Tc-CRIP imaging was used to evaluate the therapeutic effects of captopril, losartan, and spironolactone, individually or in combination. 62 Radiotracer infarct uptake of 2.3% injected dose per gram of tissue (%ID/g) in untreated animals reduced to 1.7% ID/g by single treatment using any of the 3 drugs and further reduced by a combination of 2 or 3 drugs (1.31% and 1.16% ID/g, respectively). As in the previous study, radiotracer uptake correlated with the extent of myofibroblast accumulation and the presence of newly formed collagen fibers; the treatment did not reduce collagen formation in the scar.…”
Section: Imaging Myofibroblasts and Rasmentioning
confidence: 99%
“…In the subsequent study, 99m Tc-CRIP imaging was used to evaluate the therapeutic effects of captopril, losartan, and spironolactone, individually or in combination. 62 Radiotracer infarct uptake of 2.3% injected dose per gram of tissue (%ID/g) in untreated animals reduced to 1.7% ID/g by single treatment using any of the 3 drugs and further reduced by a combination of 2 or 3 drugs (1.31% and 1.16% ID/g, respectively). As in the previous study, radiotracer uptake correlated with the extent of myofibroblast accumulation and the presence of newly formed collagen fibers; the treatment did not reduce collagen formation in the scar.…”
Section: Imaging Myofibroblasts and Rasmentioning
confidence: 99%
“…Baseline strain (␤ ϭ 0.47, p Ͻ 0.0001), spironolactone therapy (␤ ϭ Ϫ0.38, p Ͻ 0.0001), and change in PICP level (␤ ϭ Ϫ0. 19, p Ͻ 0.03) were independently associated with LV systolic function improvement (increase in strain). Correlates of LV diastolic function improvement (increase in early diastolic mitral annular velocity) were baseline early diastolic mitral annular velocity (␤ ϭ 0.47, p Ͻ 0.0001), spironolactone therapy (␤ ϭ Ϫ0.…”
mentioning
confidence: 93%
“…14 Preclinical studies have shown feasibility of visualizing avb 3 integrin 15,16 (on myofibroblasts), angiotensin-converting enzyme (ACE), 17 angiotensin II receptor type 1 (AT1), 18 and coagulation factor XIII. 19 Although initial small scale clinical pilot studies have been performed for some of these tracers, [20][21][22] no definitive studies have been performed.…”
Section: See Related Article Pp 1114-1123mentioning
confidence: 99%